Precipitation and Stabilization of Alumina Precursor Powders Using Urea and Polyacrylate - Alexandre Monteiro (The Minerals, Metals and Materials Society, 1994)
Alumina precursor powders can be precipitated from aqueous solutions, using hydrothermal decomposition of urea to deliver base homogeneously to the system. Primary particles agglomerate early in the process, generating a wide size distribution. The presence of a polymeric surfactant such as polyacrylate can suppress or delay agglomeration, reducing particle size and narrowing the size distribution. The stabilization of commercially available a-Alp03 powder with polyacrylate was studied, investigating the effects of polyacrylate molecular weight, ionic strength and temperature. The effect of aluminum concentration, polyacrylate molecular weight and urea concentration on the precipitation of alumina precursors in a sulfate- urea system in the presence of polyacrylate/polyacrylic acid was then studied. The hydrolysis kinetics were followed, and particle sizes were determined. Precipitates were further characterized using energy dispersive spectroscopy. The particle characteristics are discussed in terms of the process conditions.